Antecedents of Accelerated Internationalisation of Polish and Czech Small and Medium-Sized Enterprises - Izabela Kowalik; Lidia Danik; Petr Král; Hana Řezanková (Entrepreneurial Business and Economics Review)
Objective: The study goal was the investigation of relationships between accelerated internationalisation descriptors and antecedent firm- and entrepreneur-related factors in Polish and Czech SMEs.